Ecotheology in the Perspective of Islamic Education: A Conceptual Review - Syafaruddin, Baso (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Massive environmental degradation, climate change, and other ecological crises demand responses that are not only technocratic but also transformative in terms of values and worldview. Islamic education with an ecotheology paradigm can be an instrument of social transformation towards a more sustainable and ecologically just civilization. Therefore, this study aims to underscore the growing urgency of incorporating ecotheology into Islamic education in the Anthropocene era. With a qualitative approach and literature review, this work reveals that ecotheology in Islamic education requires a holistic and integrated approach, from the philosophical to the practical level. The curriculum, learning methods, and the role of educators must be aligned to create a transformative learning experience. The existing challenges can be overcome through a comprehensive strategy and strong commitment from all stakeholders. Islamic education that integrates ecotheology will be able to produce a generation of Muslims who are not only individually pious but also have high ecological awareness and responsibility. They will become agents of change who can contribute to building a sustainable and ecologically just civilization.